Impact on Life Expectancy of Withdrawing Thiopurines in Patients with Crohn’s Disease in Sustained Clinical Remission: A Lifetime Risk-Benefit Analysis - Kirchgesner, Julien (PLoS One, 2016)
OBJECTIVE: Long-term treatment with thiopurines is associated with a decreased risk of Crohn’s disease (CD) flare but an increased risk of various cancers depending on gender, age, and presence of extensive colitis. We evaluated risks and benefits of withdrawing thiopurines in patients with CD in prolonged remission. METHODS: We developed a Markov model assessing risks and benefits of withdrawing thiopurines compared to continuing thiopurines in a lifetime horizon. The model was stratified by age (35 and 65 years old at thiopurine withdrawal), gender and presence of extensive colitis. Parameter estimates were taken from French cohorts and hospital databases, cancer and death national registries and published literature. Life expectancy, rates of relapse, serious adverse events, and causes-of-death were evaluated. RESULTS: In patients without extensive colitis, continuing thiopurines increased life expectancy up to 0.03 years for 35 year-old men and women but decreased life expectancy down to 0.07 years for 65 year-old men and women. Withdrawal strategy became the preferred strategy at 40.6 years for men, and 45.7 years for women without extensive colitis. In patients with extensive colitis, continuation strategy was the preferred strategy regardless of age. Risk-benefit analysis was not modified by duration of CD activity. CONCLUSIONS: Factors determining life expectancy associated with withdrawal or continuation of thiopurines in patients with CD and in sustained clinical remission vary substantially according to gender, age and presence of extensive colitis. Individual decisions to continue or withdraw thiopurines in patients with CD in sustained remission should take into account these parameters.